Digital Government Excellence: Lessons from Effective Digital Leaders - Sikkut, Siim (Wiley CIO series, 2022)
How to lead the digital transformation of governments Digital Government Excellence: Lessonsfrom Effective Digital Leaders delivers a fascinating treatment of digital leadership as governments around the world start or restart the digital transformation of their work and service delivery. The author provides a playbook on how to achieve digital excellence via interviews with 20 remarkable digital government leaders from around the world. Each one offers insights on strategies for how to incorporate the best of digital into public services and practical tips on leading digital reforms and delivery teams. The book also: * Explores how to begin the task of making all of government to "go digital" or go deeper and bolder in this direction, including the first steps and beyond * Highlights leadership styles and practices for effective and lasting delivery of digital strategies and reforms * Provides food for thought about whatit takes to be an impactful digital transformation leader – in government and beyond The book is ideal for Chief Digital/Information/Technology Officers or digital agency leaders in public service. Digital Government Excellence is also an indispensable resource for any practitioner, policymaker or political leader in governments at any level, as well as any student or advisor of governments looking intohow to deliver digital transformation in the public sector.